Cow Based Inputs for Sustainable Agriculture: A Review - , Koyi Jyothsna; Aakash,; Jayadeva, H. M.,; , Mahantesh B. Nagangoudar (Archives of Current Research International, 2024)
Food safety is of prime importance at present because the consumption of food products with chemical residues above the threshold levels is causing dreadful diseases in living beings and deteriorating soil health too. The current global scenario firmly emphasizes the need to adopt agricultural practices that are ecologically safe for sustainable food production. Hence, it is necessary to adopt organic farming which improves the health of Agro-ecosystems besides providing safe food and conserving the soil fertility and soil biota. There is a need to identify a suitable substitute in place of chemical fertilizers which are economically cheaper and ecofriendly. In this context, Cow-based inputs (dung, urine, ghee, milk) play an important role in organic farming as an alternative to chemical fertilizers which help in the growth of the crop and provide eco-safety food